Mechanism of curaxin-dependent nucleosome unfolding by FACT - Volokh, Olesya I.; Sivkina, Anastasia L.; Moiseenko, Andrey V.; Popinako, Anna V.; Karlova, Maria G.; Valieva, Maria E.; Kotova, Elena Y.; Kirpichnikov, Mikhail P.; Formosa, Timothy; Studitsky, Vasily M.; Sokolova, Olga S. (Frontiers in Molecular Biosciences, 2022)
Human FACT (FACT) is a multifunctional histone chaperone involved in transcription, replication and DNA repair. Curaxins are anticancer compounds that induce FACT-dependent nucleosome unfolding and trapping of FACT in the chromatin of cancer cells (c-trapping) through an unknown molecular mechanism. Here, we analyzed the effects of curaxin CBL0137 on nucleosome unfolding by FACT using spFRET and electron microscopy. By itself, FACT adopted multiple conformations, including a novel, compact, four-domain state in which the previously unresolved NTD of the SPT16 subunit of FACT was localized, apparently stabilizing a compact configuration. Multiple, primarily open conformations of FACT-nucleosome complexes were observed during curaxin-supported nucleosome unfolding. The obtained models of intermediates suggest “decision points” in the unfolding/folding pathway where FACT can either promote disassembly or assembly of nucleosomes, with the outcome possibly being influenced by additional factors. The data suggest novel mechanisms of nucleosome unfolding by FACT and c-trapping by curaxins.